Stem‐cell–based therapies to enhance peripheral nerve regeneration. Issue 4 (3rd December 2019) - Kubiak, Carrie A.; Grochmal, Joey; Kung, Theodore A.; Cederna, Paul S.; Midha, Rajiv; Kemp, Stephen W.P.
Abstract: Peripheral nerve injury remains a major cause of morbidity in trauma patients. Despite advances in microsurgical techniques and improved understanding of nerve regeneration, obtaining satisfactory outcomes after peripheral nerve injury remains a difficult clinical problem. There is a growing body of evidence in preclinical animal studies demonstrating the supportive role of stem cells in peripheral nerve regeneration after injury. The characteristics of both mesoderm‐derived and ectoderm‐derived stem cell types and their role in peripheral nerve regeneration are discussed, specifically focusing on the presentation of both foundational laboratory studies and translational applications. The current state of clinical translation is presented, with an emphasis on both ethical considerations of using stems cells in humans and current governmental regulatory policies. Current advancements in cell‐based therapies represent a promising future with regard to supporting nerve regeneration and achieving significant functional recovery after debilitating nerve injuries.